UMPSA receives Proton X50 for teaching and learning - Naqiah, Puaad (UMPSA, 2025)
PEKAN, 13 June 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) received a new boost in its effort to strengthen teaching and learning based on automotive technology when it received two Proton X50 vehicles from the national car manufacturer, PROTON, recently.